Bupleurum chinense polysaccharide inhibit adhesion of human melanoma cells via blocking β1 integrin function. (20th January 2017) - Tong, Haibin; Jiang, Guiquan; Qi, Dake; Bi, Jingfeng; Tian, Dan; Guan, Xingang; Zheng, Sheng; Sun, Xin
Highlights: BCP, water-soluble polysaccharide extracted from Bupleurum chinense, inhibited integrin-mediated adhesion of human melanoma A375 cells to fibronectin but had no effects on nonspecific adhesion to poly-l -lysine. BCP-treatment reduced β1 integrin ligand affinity and inhibited the adhesion-dependent formation of F-actin stress fibers and focal adhesions. The inhibition of BCP on integrin-mediated signaling is probably through its dephosphorylatory effects on focal adhesion kinase (FAK) and paxillin. Our current findings indicated that BCP may be a potential therapy for melanoma metastasis due to its inhibitory effects on integrin signaling. Abstract: Adhesive interaction contributes toward tumor metastasis and the transmembrane glycoprotein receptor, integrin has been recognized to mediate the adhesion to extracellular matrix thus upregulating tumor metastasis. In the current study, we evaluated the anti-adhesive mechanisms of a water-soluble polysaccharide (BCP) extracted from Bupleurum chinense . BCP inhibited integrin-mediated adhesion of human melanoma A375 cells to fibronectin but had no effects on nonspecific adhesion to poly-l -lysine. BCP also reduced β1 integrin ligand affinity for GST-FNIII9-10 proteins. The adhesion-dependent formation of F-actin stress fiber and focal adhesion (FA) was also inhibited by BCP treatment. The inhibition of BCP on integrin-mediated signaling is probably through inhibiting phosphorylation of focal adhesion kinase (FAK) and paxillin. Collectively, our current findings indicated that BCP may be a potential therapy for melanoma metastasis due to its inhibitory effects on integrin function.